Morphological Changes in the Heart with Clozapine Poisoning (Experimental Study) - O. L. Romanova; D. V. Sundukov; A. M. Golubev; A. S. Babkina; M. A. Golubev (Общая реаниматология, 2017)
Objective: to identify histomorphological changes in the heart for acute poisoning with clozapine and combined poisonings with ethanol and clozapine 3 and 24 hours after poisoning. Materials and methods: the experiments were performed in mongrel male rats weighing 290—350 g. Clozapine was administered at a dose of 150 mg/kg animal weight under anesthesia with chlorolase. After 3 hours and 24 hours the animals were sacrificed by decapitation. Histological sections of the heart of 5 rats that had received clozapine orally at a dose of 150 mg/kg and of 5 rats that had received ethanol and clozapine orally in the above doses 3 hours after the poisoning were examined. There was also a study of histological sections of the heart of rats (n=10) that had received similar preparations in the above doses and were withdrawn from the experiment 24 hours after the administration of the preparations. The comparison was performed by evaluating the histological sections of the heart of rats (n=5) that had not received the above substances. The presence of following morphological signs was evaluated: circulatory disorders (plethora, hemorrhages), eosinophilia, fragmentation of cardiomyocytes, cell reaction, and homogeneity of the cytoplasm. The evaluation was carried out using the Fisher criterion. The presence of a sign was considered reliable when it appeared in 4—5 cases in one group and was completely absent in another. Results: in the control group of animals the histological examination of the heart showed no circulatory disorders, eosinophilia, fragmentation of cardiomyocytes, or homogeneity of the cytoplasm. The earliest change in the heart with the effect of clozapine was blood circulation disorders that appeared already 3 hours after the administration of the medicine and increased by 24 hours. Eosinophilia of the myocardium, which is specific for clozapine poisoning, was observed in all experimental groups. In the clozapine and ethanol group, homogenization of the cytoplasm was observed after 3 hours, indicating cell death. In the group receiving clozapine as a monopreparation, similar changes were not observed. Perhaps, the appearance of such changes is associated with the influence of ethanol. In the group affected by clozapine and ethanol there were circulatory disorders (plethora of veins and venules, small pericapillary hemorrhages) after 3 hours. By 24 hours these disorders intensified. Arterial and venous plethora, periarterial and pericapillary hemorrhages were observed. Conclusion. The changes revealed by histological examination of the heart in animals receiving clozapine and a combination of ethanol and clozapine, together with the results of forensic analysis, can be used to diagnose relevant poisonings and to establish their prescription.